2002
DOI: 10.1177/104365960201300104
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Microbicides for HIV/STI Prevention in Zimbabwe: What Key Informants Say

Abstract: The purpose of this study was to assess the acceptability of vaginal microbicides as prevention methods for heterosexually transmitted HIV. Interviews were conducted with key informants in and around Harare using a semistructured questionnaire with probes. Twenty-seven interviews were conducted with a total of 48 informants. Most women were enthusiastic about the products but had concerns about safety and how the use of these products might affect their relationships with their husbands. Many men were concerne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 4 publications
1
12
0
1
Order By: Relevance
“…M. Montgomery et al, 2008;Moon et al, 2002;Veldhuijzen et al, 2006;Venables & Stadler, 2012;C. Woodsong & Alleman, 2008).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…M. Montgomery et al, 2008;Moon et al, 2002;Veldhuijzen et al, 2006;Venables & Stadler, 2012;C. Woodsong & Alleman, 2008).…”
Section: Discussionunclassified
“…Woodsong et al, 2013). One prominent issue from these studies is the role male partners play in the use of vaginal microbicide (Doggett et al, 2015;Jones, Weiss, Chitalu, Bwalya, & Villar, 2008;Koo, Woodsong, Dalberth, Viswanathan, & Simons-Rudolph, 2005;Lanham et al, 2014; C. M. Montgomery et al, 2010; C. M. Montgomery et al, 2008;Moon, Khumalo-Sakutukwa, Heiman, Mbizvo, & Padian, 2002;Venables & Stadler, 2012;C. Woodsong & Alleman, 2008;Cynthia Woodsong & Holt, 2015; C. Woodsong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the reaction of men in Zimbabwe, it has been suggested that 'Many men were concerned that women would be able to use the products without their consent or knowledge. Several products may be acceptable in this culture but must be introduced within the existing gender power structure' [10]. Microbicides will, of course, have to be introduced within existing gender power structures in every culture, not just Zimbabwe.…”
Section: Contextual Microbicide Usage Must Be Considered In Their Devmentioning
confidence: 99%
“…Work in Zimbabwe (Moon et al 2002) have revealed that there is an urgent need for both spermicidal and non-spermicidal microbicides to be made available, especially in contexts where fertility is still highly valued. In settings such as those described here, where sperm are highly valued, microbicides might represent a real alternative to condoms (both male and female) for HIV prevention.…”
Section: Condoms As Non-maasaimentioning
confidence: 99%